Influences on single-use and reusable cup use: a multidisciplinary mixed-methods approach to designing interventions reducing plastic waste. Issue 3 (22nd September 2021) - Allison, Ayşe Lisa; Lorencatto, Fabiana; Miodownik, Mark; Michie, Susan
Abstract : An estimated 2.5–5 billion single-use coffee cups are disposed of annually in the UK, most of which consist of paper with a plastic lining. Due to the difficulty of recycling poly-coated material, most of these cups end up incinerated or put in landfills. As drinking (take-away) hot beverages is a behaviour, behaviour change interventions are necessary to reduce the environmental impacts of single-use coffee cup waste. Basing the design of interventions on a theoretical understanding of behaviour increases the transparency of the development process, the likelihood that the desired changes in behaviour will occur and the potential to synthesise findings across studies. The present paper presents a methodology for identifying influences on using single-use and reusable cups as a basis for designing intervention strategies. Two behaviour change frameworks: The Theoretical Domains Framework (TDF) and the Capability-Opportunity-Motivation-Behaviour (COMB) model of behaviour, were used to develop an online survey and follow-up interviews. Research findings can inform the selection of intervention strategies using a third framework, the Behaviour Change Wheel (BCW). The application of the methodology is illustrated in relation to understanding barriers and enablers to single-use and reusable cup use across the setting of a London university campus. We have developed a detailed method for identifying behavioural influences relevant to pro-environmental behaviours, together with practical guidance for each step and a worked example. Benefits of this work include it providing guidance on developing study materials and collecting and analysing data. We offer this methodology to the intervention development and implementation community to assist in the application of behaviour change theory to interventions.